2018
DOI: 10.1002/jper.17-0550
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration with bovine bone impairs orthodontic tooth movement despite proper osseous wound healing in a novel mouse model

Abstract: The two novel mouse models show that the lack of resorption of BB xenografts renders them inadequate for proper orthodontic tooth movement at a later stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…A total of 12 mice were divided randomly into 1) test group in which the sockets were filled with bovine bone (BB + , n = 6) and 2) control group in which the sockets remained without graft filling (BB – , n = 6). All mice were sacrificed after 7 wk based on our previous study (Klein, Fleissig, et al 2019), which showed full osseous healing at 4 wk after bone regeneration.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 12 mice were divided randomly into 1) test group in which the sockets were filled with bovine bone (BB + , n = 6) and 2) control group in which the sockets remained without graft filling (BB – , n = 6). All mice were sacrificed after 7 wk based on our previous study (Klein, Fleissig, et al 2019), which showed full osseous healing at 4 wk after bone regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…Bovine bone was pulverized coarsely with a sterile mortar and pestle as we previously described (Klein, Fleissig, et al 2019). The bovine bone particles size was measured under light microscopy with a mean diameter of 56.07 ± 29.46 µm and stored at room temperature until use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations